PERENCANAAN PENANGANAN PERIZINAN PEMBANGUNAN TAMAN WISATA ALAM PEMANDIAN MEGA MENDUNG NAGARI SINGGALANG KABUPATEN TANAH DATAR - Reffishandria Lisna Kurniawan; M Fachri Adnan (Jurnal Teori dan Riset Administrasi Publik, 2024)
This research is motivated by the natural tourist park tourist attraction which is located on the Sicincin-Bukittinggi highway, precisely in the Anai Valley, where the location of this tourist attraction is included in a natural conservation area. This research aims to design a planning for handling permits for the construction of the Mega Mendung Natural Tourism Park in Nagari Singgalang, Tanah Datar Regency. This research focuses on analyzing licensing regulations, mapping licensing procedures, and preparing recommendations to simplify and speed up the licensing process for developing Nature Tourism Parks. The research methodology involved data collection, regulatory analysis, interviews, and field surveys. The results of this research show that the government is taking a middle path to resolve licensing issues in the form of managing natural conservation areas in accordance with existing regulations, while the entrepreneurs themselves will later follow government decisions in the future considering that this tourist attraction has been operating for quite a long time and without an official permit.